2003
DOI: 10.1023/b:aibe.0000004730.62934.ed
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of HIV Sexual Risk Behaviors in a Community Sample of Injection Drug-Using Men and Women

Abstract: Injection risk practices and unprotected sex between injection drug users (IDUs) and their sexual partners are responsible for a high proportion of AIDS cases and new HIV infections in the United States. The purpose of this study was to investigate the links between drug use behaviors and psychosocial factors with high-risk sexual behaviors among male and female IDUs. Understanding the determinants of sexual risk practices among drug users can lead to the development of more effective programs to prevent sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 18 publications
3
39
1
Order By: Relevance
“…13 Our finding that IDUs practicing higher injection-related risk behavior are more likely to be practicing higher sexual risk behavior is consistent with other research findings. [14][15][16][17][18][19] There is some evidence from other studies in line with our results that those injecting buprenorphine might have lower HIV-related risky injection practices. [20][21] A study carried out recently by Otiashvili et al among IDUs in Georgian needle exchange programs found that two thirds of IDUs injected buprenorphine in the past month and approximately a half of these used it to cope with the symptoms of withdrawal.…”
Section: Discussionsupporting
confidence: 90%
“…13 Our finding that IDUs practicing higher injection-related risk behavior are more likely to be practicing higher sexual risk behavior is consistent with other research findings. [14][15][16][17][18][19] There is some evidence from other studies in line with our results that those injecting buprenorphine might have lower HIV-related risky injection practices. [20][21] A study carried out recently by Otiashvili et al among IDUs in Georgian needle exchange programs found that two thirds of IDUs injected buprenorphine in the past month and approximately a half of these used it to cope with the symptoms of withdrawal.…”
Section: Discussionsupporting
confidence: 90%
“…Hence, Meth-pretreated males did not have impaired associative memory or reduced sensitivity to LiCl or LiCl-induced illness. It appears that Meth pretreatment caused maladaptive or compulsive sex seeking, despite learned negative consequences, which is in line with human reports (Frosch et al, 1996;Halkitis et al, 2001;McKirnan et al, 2001;Rawson et al, 2002;Somlai et al, 2003;Green and Halkitis, 2006;Springer et al, 2007).…”
Section: Discussionsupporting
confidence: 82%
“…Drug use is a determinant of high-risk behavior and infection, [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] and substantial proportions of the US prison population report a history of heavy drug and alcohol use. 48 The effect of incarceration on STI/HIV risk may differ by drug use status.…”
mentioning
confidence: 99%